2009
DOI: 10.1051/0004-6361/200911789
|View full text |Cite
|
Sign up to set email alerts
|

Structure and spectra of irradiated secondaries in close binaries

Abstract: Context. The standard stellar model atmosphere ignores the influence of external radiation. This assumption, while sufficient for most stars, fails for many short-period binaries. Aims. In setting up combined model atmospheres for close binaries, we want to constrain the parameters of both components, especially in the case of a hot primary component strongly influencing its cool secondary companion. This situation can be found after common envelope evolution (CEE). The status of both components today allows o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…a (Kurucz 1979) subgiant. However the day-side temperature in irradiated models can reach factors of between four and ten times larger than the shadowed side (e.g., Wawrzyn et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…a (Kurucz 1979) subgiant. However the day-side temperature in irradiated models can reach factors of between four and ten times larger than the shadowed side (e.g., Wawrzyn et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To model the effects of irradiation and reproduce both the spectral variations and the reflection effect in the light curve of AA Dor, we followed the description of the geometry of eclipsing binaries developed by Günther & Wawrzyn (2011) and Wawrzyn et al (2009) (2011), we adopted the same spherical coordinate system with the origin at the centre of the secondary star and the z-axis intersecting the centre of the primary. The z-axis intersects the surface of the companion at the substellar point, where irradiation is the strongest.…”
Section: Modelling the Spectrum Of The Irradiated Secondarymentioning
confidence: 99%
“…2.3). Wawrzyn et al (2009) suggested the enriched C and N abundance required to reproduce the strong lines may be the result of polluted material accreted from the primary. NGC 6326 is also one of a few post-CE binaries showing the higher ionisation C IV lines (Pollacco & Bell 1994;Corradi et al 2011;Miszalski et al 2011b).…”
Section: Gemini South Gmos Spectroscopy Of Ngc 6326mentioning
confidence: 99%